The Role of General Election Commission (KPU) in Increasing Voters’ Participation in Langkat, Medan, Indonesia - Dedi Amrizal; Yusriati Yusriati; Hermansyah Lubis (Budapest International Research and Critics University, 2018)
Voter participation in elections is one of the benchmarks of the success of political development. The high level of voter participation will indicate the success of the elections and the low voter participation will indicate the failure of the election. Therefore, it is necessary to increase the participation of the voters as the responsibility of the KPU. Therefore, the KPU makes an effort to increase voter participation by conducting election socialization in Langkat Regency. The socialization aims to provide and disseminate information on elections. The effort is certainly to increase voter participation in the election. From this research is done with the aim to know the role of Election Commission Langkat in order to increase voter participation. The method used in this research is descriptive research method with qualitative approach. Analysis of the whole data is done with summarize data that is selecting data, simplified, and taken the main meaning (essence). Based on measurement of effectiveness of election socialization such as; achievement of objectives, procedures, resources, budgets, facilities, infrastructure and integration or cooperation with other organizations. Generated that socialization of election conducted by Langkat Regency KPU not yet effective where achievement of objective, procedure, budget, infrastructure and integration not effective and utilization of resources and facilities running effectively. So the result of this research is the role of Election Commission Langkat in order to increase the voters have not been maximized. With low voter participation rate around 60% obtained by data processing KPU Langkat Regency.